If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = -1x + -4x + 4 Reorder the terms: 29 = 4 + -1x + -4x Combine like terms: -1x + -4x = -5x 29 = 4 + -5x Solving 29 = 4 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 29 + 5x = 4 + -5x + 5x Combine like terms: -5x + 5x = 0 29 + 5x = 4 + 0 29 + 5x = 4 Add '-29' to each side of the equation. 29 + -29 + 5x = 4 + -29 Combine like terms: 29 + -29 = 0 0 + 5x = 4 + -29 5x = 4 + -29 Combine like terms: 4 + -29 = -25 5x = -25 Divide each side by '5'. x = -5 Simplifying x = -5
| 3+1x=11 | | 14+3G=8n-3(n-4) | | 9w+9=3w+15 | | y=-3x^2-6x | | w=0.3d-0.5 | | 3x-y=-6 | | y=160-x | | x^2-.25x-16=0 | | 3(6n-5)= | | 4x-4=32 | | 2x+12=3x | | 7(x+5)= | | -8+2x-7x=-68 | | 8x^3+20x^2= | | 7x-1=26-2x | | (x+5)(x+5)=75 | | 2x^2=9x+5 | | 3m+2m+20=5m | | 17=5(3+w)+7 | | 6x^2+y^2=36 | | 12x-144=0 | | 30x=50x+1.5 | | x^2+x=5 | | 6-8y=-26 | | -3(8x+2)=-8(-3+3x) | | x*x*x-x=60 | | (.5)(x+3)(x)=20 | | 8x-24=0 | | 9g-11=2g+38 | | (.5)(x+3)(x)=0 | | -5x-3+4x=-3 | | 63=8w+2.6-3.6 |